The pharmacology and mechanisms of platycodin D, an active triterpenoid saponin from Platycodon grandiflorus - Xie, Long; Zhao, Yu-Xin; Zheng, Yu; Li, Xiao-Fang (Frontiers in Pharmacology, 2023)
Chinese doctors widely prescribed Platycodon grandiflorus A.DC. (PG) to treat lung carbuncles in ancient China. Modern clinical experiences have demonstrated that PG plays a crucial role in treating chronic pharyngitis, plum pneumonia, pneumoconiosis, acute and chronic laryngitis, and so forth. Additionally, PG is a food with a long history in China, Japan, and Korea. Furthermore, Platycodin D (PLD), an oleanane-type triterpenoid saponin, is one of the active substances in PG. PLD has been revealed to have anti-inflammatory, anti-viral, anti-oxidation, anti-obesity, antico-agulant, spermicidal, anti-tumor etc., activities. And the mechanism of the effects draws lots of attention, with various signaling pathways involved in these processes. Additionally, research on PLD's pharmacokinetics and extraction processes is under study. The bioavailability of PLD could be improved by being prescribed with Glycyrrhiza uralensis Fisch. or by creating a new dosage form. PLD has been recently considered to have the potential to be a solubilizer or an immuno-logic adjuvant. Meanwhile, PLD was discovered to have hemolytic activity correlated. PLD has broad application prospects and reveals practical pharmacological activities in pre-clinical research. The authors believe that these activities of PLD contribute to the efficacy of PG. What is appar-ent is that the clinical translation of PLD still has a long way to go. With the help of modern technology, the scope of clinical applications of PLD is probable to be expanded from traditional applications to new fields.